2022
DOI: 10.3389/frhs.2022.818519
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Improving Access to Cancer Services in Rural Communities: A Pre-implementation Study

Abstract: BackgroundImplementation science is defined as the scientific study of methods and strategies that facilitate the uptake of evidence-based practice into regular use by practitioners. Failure of implementation is more common in resource-limited settings and may contribute to health disparities between rural and urban communities. In this pre-implementation study, we aimed to (1) evaluate barriers and facilitators for implementation of guideline-concordant healthcare services for cancer patients in rural communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Our survey identified that CAHs are regularly 39 collaborating with community organizations to support CAH capacity to meet patients' needs before and during a cancer diagnosis, especially by providing resources for cancer screening, education, and awareness, as well as support services for individuals with cancer and their families. To further enhance this capacity, we can look to previous work on models of cancer care coordination in rural settings, which promote models of cross‐region provider collaboration and care coordination 40 . In 2019, the American Society of Clinical Oncology hosted a forum titled Closing the Rural Cancer Care Gap, which looked for opportunities and best practices, noting a number of opportunities related to care coordination including working with community leaders to assess local gaps in cancer care and provide community‐based solutions 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey identified that CAHs are regularly 39 collaborating with community organizations to support CAH capacity to meet patients' needs before and during a cancer diagnosis, especially by providing resources for cancer screening, education, and awareness, as well as support services for individuals with cancer and their families. To further enhance this capacity, we can look to previous work on models of cancer care coordination in rural settings, which promote models of cross‐region provider collaboration and care coordination 40 . In 2019, the American Society of Clinical Oncology hosted a forum titled Closing the Rural Cancer Care Gap, which looked for opportunities and best practices, noting a number of opportunities related to care coordination including working with community leaders to assess local gaps in cancer care and provide community‐based solutions 21 …”
Section: Discussionmentioning
confidence: 99%
“…To further enhance this capacity, we can look to previous work on models of cancer care coordination in rural settings, which promote models of cross-region provider collaboration and care coordination. 40 In 2019, the American Society of Clinical Oncology hosted a forum titled Closing the Rural Cancer Care Gap, which looked for opportunities and best practices, noting a number of opportunities related to care coordination including working with community leaders to assess local gaps in cancer care and provide community-based solutions. 21 Going forward, there are a variety of innovative ways in which CAHs may further confront the cancer care needs of their rural communities, including by building relationships with non-local providers and using telemedicine to improve barriers in access.…”
Section: Discussionmentioning
confidence: 99%
“… 14 While services are commonly available in comprehensive cancer care settings, once patients conclude treatment and resume routine healthcare follow up in their community, specialized support services are lacking. 15 This is especially true in rural areas of the US, where access to supportive care providers with expertise in oncology is limited. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] There is a large evidence base documenting communitybased and culturally relevant approaches to cancer care in historically marginalized populations. [27][28][29][30][31][32] Although programs exist that focus on expanding access based upon particular cancers [33][34][35][36] or on disease-specific integration of care, 37 broad-based access programs have been more challenging to establish and sustain. 38 To date, there are few community-based clinical interventions that expand access to a National Cancer Institute (NCI)-Designated Cancer Center across disease types.…”
Section: Introductionmentioning
confidence: 99%